Problematika Pembelajaran Bahasa Arab Di Madrasah Diniyah (MD) Nurul Iman - Muhammad Hidayatullah (Tihamah: Jurnal Studi Islam, 2023)
Problems with learning Arabic have become something that should be resolved and overcome by teachers and students. Problems with learning Arabic can occur from internal and external factors. This was experienced by students at Madrasah Diniyah (MD) Nurul Iman Majalengka. The purpose of this research is to find out the causes of problems in learning Arabic, find out the role of educators in overcoming obstacles to learning Arabic, and find solutions to obstacles to learning Arabic. This research uses a qualitative approach with descriptive research type. The research was conducted using in-depth interviews. The results of the research show that students experience problems in learning Arabic, they do not memorize Arabic letters, there are no handbooks for students, there is no interest in learning Arabic, it is difficult to memorize Arabic vocabulary, and it is difficult to pronounce the appropriate Arabic letters. Educators try to provide additional study hours, photocopy textbooks, and provide motivation in overcoming the problems of learning Arabic. The solution given is to change the Arabic language study hours to 14.15-17.30, charging a fee of IDR 10,000 to each student to support learning needs; implementing learning using video media, and full support from parents.